Oxaliplatin and [Pt(R, R-DACH)(panobinostat-2H)] show nanomolar cytotoxicity towards diffuse intrinsic pontine glioma (DIPG). Issue 17 (16th April 2020) - Boulet, Marie H. C.; Marsh, Laura K.; Howarth, Alison; Woolman, Alice; Farrer, Nicola J.
Abstract : Oxaliplatin and the platinum(ii ) panobinostat complex (2 ) demonstrate nanomolar cytotoxicity towards diffuse intrinsic pontine glioma cells (DIPG); with 2 exhibiting improved solubility in comparison to panobinostat. Abstract : We report the synthesis of two novel platinum(ii ) complexes which incorporate histone deacetylase (HDAC) inhibitors: [Pt II ( R, R -DACH)(Sub-H )] (1 ), [Pt II ( R, R -DACH)(panobinostat-2H )] (2 ), where SubH = suberoyl-bis-hydroxamic acid; DACH = (1 R, 2 R )-(–)-1, 2-diaminocyclohexane and panobinostat = ( E )- N -hydroxy-3-[4-[[2-(2-methyl-1 H -indol-3-yl)ethylamino]methyl]phenyl]prop-2-enamide. Complexes 1 and 2 were characterised by 1 H, 13 C, 195 Pt NMR spectroscopy and ESI-MS. Whilst oxaliplatin demonstrated considerable cytotoxicity in two patient-derived low-passage paediatric glioma DIPG cell lines (IC50 values of 0.333 μM in SU-DIPG-IV, and 0.135 μM in SU-DIPG-XXI), complex 2 showed even greater cytotoxicities, with IC50 values of 0.021 μM (SU-DIPG-IV), 0.067 μM (BIOMEDE 194) and 0.009 μM (SU-DIPG-XXI). Complex 2 also demonstrated superior aqueous solubility in comparison to panobinostat. Complex 2 released free intact panobinostat under HPLC conditions, as determined by ESI-MS. Incubation of solutions of oxaliplatin (H2 O) and panobinostat (DMF) resulted in instantaneous reactivity and precipitation of a panobinostat derivative which was not a platinum complex; the same reactivity was not observed between carboplatin and panobinostat.